Complicities A theory for subjectivity in the psychological humanities - Distiller, Natasha (Palgrave Studies in the Theory and History of Psychology, 2022)
This is the kind of writing - I hope - members of allied health and medical disciplines have been waiting for. Complicities offers a gentle, generous, highly knowledgeable, and accessible introduction to and application of transdisciplinarity at its best. Using argumentsand ideas from the critical humanities and cutting-edge approaches to neurobiology and psychotherapy, Natasha Distiller invites the reader into a world in which diversity and complexity are openly at play and the taken-for-granted is given a chance to dissolve. -David Azul, La Trobe University, Bendigo, Australia Beginning from the premise that we cannot separate ourselves from the systems that precede and formulate us as subjects, the author argues that, in reckoning with this complicity, a model of subjectivity can be created that moves beyond binaries and identity politics. In doing so, the book examines how we might develop a more socially just psychological theory and practice, which is both systems work and intra-psychological work. In bringing together ways of thinking developed in the humanities with clinical psychotherapeutic practice, this book offers one interdisciplinary take on key questions of social and emotional efficacy in action-oriented psychotherapy work. Natasha Distiller is a psychotherapist in private practice in Berkeley, California. She is a lecturer in the Gender and Women's Studies Department at UC Berkeleyand a Beatrice Bain Research Scholar in the department.